Transcriptional and Bioinformatic Analysis Provide a Relationship between Host Response Changes to Marek's Disease Viruses Infection and an Integrated Long Terminal Repeat - Cui, Ning (Front Cell Infect Microbiol, 2016)
GX0101, Marek's disease virus (MDV) strain with a long terminal repeat (LTR) insert of reticuloendotheliosis virus (REV), was isolated from CVI988/Rispens vaccinated birds showing tumors. We have constructed a LTR deleted strain GX0101ΔLTR in our previous study. To compare the host responses to GX0101 and GX0101ΔLTR, chicken embryo fibroblasts (CEF) cells were infected with two MDV strains and a gene-chip containing chicken genome was employed to examine gene transcription changes in host cells in the present study. Of the 42,368 chicken transcripts on the chip, there were 2199 genes that differentially expressed in CEF infected with GX0101 compared to GX0101ΔLTR significantly. Differentially expressed genes were distributed to 25 possible gene networks according to their intermolecular connections and were annotated to 56 pathways. The insertion of REV LTR showed the greatest influence on cancer formation and metastasis, followed with immune changes, atherosclerosis, and nervous system disorders in MDV-infected CEF cells. Based on these bio functions, GX0101 infection was predicated with a greater growth and survival inhibition but lower oncogenicity in chickens than GX0101ΔLTR, at least in the acute phase of infection. In summary, the insertion of REV LTR altered the expression of host genes in response to MDV infection, possibly resulting in novel phenotypic properties in chickens. Our study has provided the evidence of retroviral insertional changes of host responses to herpesvirus infection for the first time, which will promote to elucidation of the possible relationship between the LTR insertion and the observed phenotypes.